The empowerment of posyandu cadres in promoting exclusive breastfeeding to prevent stunting in Sukajadi Subdistrict - Melly Melly; Magdalena Magdalena; Okta Vitriani; Elvina Asnaty (Universitas Muhammadiyah Magelang, 2024)
Stunting is a condition in infants and young children where height or length is significantly below what is considered normal for their age. Stunting in early childhood can lead to difficulties in achieving physical and cognitive development in the future. Exclusive breastfeeding is one of the effective strategies to reduce the prevalence of stunting. This community service activity aimed to enhance the knowledge and skills of 30 posyandu cadres on exclusive breastfeeding. The results showed an improvement in the cadres' understanding of the material delivered, with the average knowledge score increasing from 59.16 before the training to 75.5 afterward. Similarly, the average skill score also increased from 38.66 before the practice to 69.1 after the practice session.